2017
DOI: 10.2147/copd.s150853
|View full text |Cite
|
Sign up to set email alerts
|

Geographical distribution of COPD prevalence in Europe, estimated by an inverse distance weighting interpolation technique

Abstract: Existing data on COPD prevalence are limited or totally lacking in many regions of Europe. The geographic information system inverse distance weighted (IDW) interpolation technique has proved to be an effective tool in spatial distribution estimation of epidemiological variables, when real data are few and widely separated. Therefore, in order to represent cartographically the prevalence of COPD in Europe, an IDW interpolation mapping was performed. The point prevalence data provided by 62 studies from 19 coun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
51
0
6

Year Published

2018
2018
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 68 publications
(58 citation statements)
references
References 69 publications
(26 reference statements)
1
51
0
6
Order By: Relevance
“…The Global Burden of Disease (GBD) study estimated that between 1990 and 2015 the prevalence of COPD increased by 44.2% and that in 2015 COPD affected 104.7 million men and 69.7 million women globally [6]. These estimates are based on data from surveys using standardised questionnaires and spirometry such as those that have been carried out under the umbrella of the Burden of Obstructive Lung Disease (BOLD) study [7] and similar studies in Latin America [8] and Europe [9]. However, using some of the same data, the Global Health Epidemiology Reference Group concluded that the prevalence was much higher and estimated that approximately 384 million people globally had COPD in 2010 [10].…”
Section: @Erspublicationsmentioning
confidence: 99%
“…The Global Burden of Disease (GBD) study estimated that between 1990 and 2015 the prevalence of COPD increased by 44.2% and that in 2015 COPD affected 104.7 million men and 69.7 million women globally [6]. These estimates are based on data from surveys using standardised questionnaires and spirometry such as those that have been carried out under the umbrella of the Burden of Obstructive Lung Disease (BOLD) study [7] and similar studies in Latin America [8] and Europe [9]. However, using some of the same data, the Global Health Epidemiology Reference Group concluded that the prevalence was much higher and estimated that approximately 384 million people globally had COPD in 2010 [10].…”
Section: @Erspublicationsmentioning
confidence: 99%
“…For each of these countries, corresponding age bracket-specific population data were used to calculate the estimated procedure volumes, by code and in total, based on data reported for year 2016. To account for potential difference in emphysema prevalence and hence treatment incidence, we used data from a recent meta-analysis of COPD prevalence [14] that provides region-specific prevalence rates to calculate an adjustment factor. This adjustment factor (1.0 for other Western European countries, 0.810 for Northern European countries, 0.993 for Central European countries, and 0.761 for Southern European countries) was multiplied on the crude country-specific procedure volume estimate to obtain estimated total volumes.…”
Section: Approximation Of Blvr Patient Volumes In Other European Counmentioning
confidence: 99%
“…Хроническая обструктивная болезнь легких (ХОБЛ) является наиболее часто встречающимся хроническим заболеванием органов дыхания. Распространенность ХОБЛ, доказанной спирометрией, среди больных с респираторными симптомами в странах Западной Европы составляет 10-27 % [1], в России -21,8 % [2]. В связи с этим оптимизация лечения ХОБЛ является важной задачей как для клинической медицины, так и для организации здравоохранения.…”
Section: обзорыunclassified